The mobile phone addiction index: Cross gender measurement invariance in adolescents - An, Xianli; Chen, Siguang; Zhu, Liping; Jiang, Caimin (Frontiers in Psychology, 2022)
The Mobile Phone Addiction Index (MPAI) is a short instrument to assess mobile phone addiction. The Chinese version of this scale has been widely used in Chinese students and shows promising psychometric characteristics. The present study tested the construct validity and measurement invariance of the MPAI by gender in middle school adolescents. The data were collected from 1,395 high school students (females, n = 646; M age = 15.3 years). Confirmatory factor analysis (CFA) and multiple-group CFA (MG-CFA) for invariance tests were conducted on the MPAI model which consisted of 17 observed items and 4 latent factors. Findings showed that the data fit the four-factor structure model well for both males and females. Furthermore, configural, metric, scalar, and residual invariance were established by gender. The results indicated that the MPAI has acceptable psychometric properties when used in adolescents. In addition, with the strict invariance requirements being satisfied, the underlying factor scores for MPAI can be meaningfully compared across genders. To our knowledge, this study is the first attempt to test the measurement invariance of the MPAI across male and female adolescents. Our results will support future research on mobile phone addiction in adolescents.